2017
DOI: 10.7554/elife.31926
|View full text |Cite
|
Sign up to set email alerts
|

Daam2 driven degradation of VHL promotes gliomagenesis

Abstract: Von Hippel-Landau (VHL) protein is a potent tumor suppressor regulating numerous pathways that drive cancer, but mutations in VHL are restricted to limited subsets of malignancies. Here we identified a novel mechanism for VHL suppression in tumors that do not have inactivating mutations. Using developmental processes to uncover new pathways contributing to tumorigenesis, we found that Daam2 promotes glioma formation. Protein expression screening identified an inverse correlation between Daam2 and VHL expressio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 72 publications
(91 reference statements)
0
14
1
Order By: Relevance
“…The effect of DAAM1 knockdown was not notable on VHL and HIF-1α expression, whereas DAAM2 knockdown substantially increased VHL expression and consequently decreased HIF-1α expression ( Figure 3D ). This was inconsistent with previous results in glioma, which showed DAAM2-driven degradation of VHL [ 10 ]. To confirm the result, we overexpressed DAAM2 in HuH7 and HepG2, and verified the effects of DAAM2 overexpression on VHL and HIF-1α after treatment with 10 μM MG132 for 6 hr.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…The effect of DAAM1 knockdown was not notable on VHL and HIF-1α expression, whereas DAAM2 knockdown substantially increased VHL expression and consequently decreased HIF-1α expression ( Figure 3D ). This was inconsistent with previous results in glioma, which showed DAAM2-driven degradation of VHL [ 10 ]. To confirm the result, we overexpressed DAAM2 in HuH7 and HepG2, and verified the effects of DAAM2 overexpression on VHL and HIF-1α after treatment with 10 μM MG132 for 6 hr.…”
Section: Resultscontrasting
confidence: 99%
“…The knockdown of both DAAM1 and DAAM2 had blunting effects on proliferation, while the knockdown of DAAM2, instead of DAAM1, substantially decreased the invasion of HuH7 ( Figure 3B, 3C ). A previous study suggested that DAAM2 could reduce VHL expression by promoting its ubiquitination [ 10 ]. Moreover, HIF-1α is a well-accepted downstream protein regulated by VHL, and it is widely involved in the progression of numerous tumors [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several genes, including ubiquitin-specific peptidase 17-like family member 8 (USP17L8), gammaglutamyltransferase light chain 2 (GGTLC2), mucin 3A (MUC3A), CTAGE family, member 6 (CTAGE6), SCOspondin (SSPO), proline-rich protein BstNI subfamily 3 (PRB3), SLAIN motif family, member 1 (SLAIN1) and axonemal central pair apparatus protein (HYDIN), have not been extensively studied, and both their functions and the significance of their variants should be further evaluated. DAAM2 may play an important role in the occurrence and development of lung, kidney, colorectal and glioma tumours (36)(37)(38)(39). DAAM2 was found to be elevated in the acute phase of Guillain-Barre syndrome through the Wnt signalling pathway (40).…”
Section: Discussionmentioning
confidence: 99%